2023
DOI: 10.1371/journal.pone.0282809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic and environmentally friendly fungicides on powdery mildew management and the phyllosphere microbiome of cucumber

Abstract: Modern agricultural practices rely on synthetic fungicides to control plant disease, but the application of these fungicides has raised concerns regarding human and environmental health for many years. As a substitute, environmentally friendly fungicides have been increasingly introduced as alternatives to synthetic fungicides. However, the impact of these environmentally friendly fungicides on plant microbiomes has received limited attention. In this study, we used amplicon sequencing to compare the bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Berg and Koskella (2018) showed that fertilization makes a plant more vulnerable to pathogen attacks [48]. A recent study revealed that the application of tebuconazole altered the fungal microbiome by decreasing the abundant fungal members, including the potentially beneficial endophytic fungi, while NPA (Neutralized Phosphorous Acid) and sulfur had minimal impacts on the phyllosphere fungal microbiome [49]. Urbanization leads to an increase in human activities and has a strong effect on the phyllosphere microbiota [50][51][52].…”
Section: Anthropogenic Factorsmentioning
confidence: 99%
“…Berg and Koskella (2018) showed that fertilization makes a plant more vulnerable to pathogen attacks [48]. A recent study revealed that the application of tebuconazole altered the fungal microbiome by decreasing the abundant fungal members, including the potentially beneficial endophytic fungi, while NPA (Neutralized Phosphorous Acid) and sulfur had minimal impacts on the phyllosphere fungal microbiome [49]. Urbanization leads to an increase in human activities and has a strong effect on the phyllosphere microbiota [50][51][52].…”
Section: Anthropogenic Factorsmentioning
confidence: 99%
“…However, the excessive use of synthetic fungicides can result in the emergence of novel strains and outbreaks within agricultural environments, thereby adding complexity to disease control efforts. Consequently, relying on synthetic fungicides over prolonged periods is not environmentally sustainable and may prove ineffective as a long-term strategy for mitigating downy mildew disease (Wu et al, 2023). The continued use of synthetic fungicides is known to have a negative impact on non-target organisms and the soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long-term and extensive use of these chemicals resulted in myriad problems, such as, increased pathogen resistance, soil contamination, polluted environment, unsafe for health, and deteriorating ecological structures (Kautsky et al, 2000). Furthermore, the growing consumers' interest in organic fruits and their processed products is urging the search for safer alternatives to synthetic fungicides while reducing costs and protecting the environment (Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%